Sejarah dan pemikiran akuntansi syariah - Maulina, Isra (FEBI IAIN Langsa, 2022)
This paper discusses the history of the birth of sharia accounting which is inseparable from thedevelopment of Islam, the obligation to record non -cash transactions as mentioned in the QS. AlBaqarah: 282 encouraged Muslims to care about recording and gave rise to the tradition ofrecording among the people, and this was one of the factors that encouraged cooperation at thattime. History proves that accounting science has long been practiced in the Islamic world,such as the term journal, which was used during the time of the Islamic caliphate with theterm